Detecting collusion on highway procurement - Gabrielli, Maria Florencia (2013)
This paper proposes a procedure to detect collusion in asymmetric first-price procurement. The main objective is twofold. First, to provide a methodology to detect collusion using a structural approach, and second to apply the methodology to field data on procurement auctions for highway construction in California. I identify two different sets of firms as potential ring members. Relying on an exogenous number of bidders and the assumption that within each type bidders are symmetric, I find evidence supporting the collusive scheme, for the two mentioned sets of firms by comparing a model of competition and a model of collusion.